Model of value added indicators of medicinal plants to raise export potential - Sotomayor Sancho Dávila, César Rafael (2018)
This the sisseeks to increase the export potential of companies that produce medicinal plants products by designing model obtained from the ratio between the export value and the behavior of added value indicators.With information collected from primary and secondary sources, it was possible to know the subject extensively and to propose the hypothesis about the indicators and the design of the model. These hypotheses were verified by the statistical analysis of the extracted data; confirming that the indicators were correct and quantifying, the extent to which each of them contributed to the value of exports, to later formulate mathematically the relationship between the behavior of these indicators and the value of exports, achieving a model that efficiently relates these two variables.